(untitled) (Bangladesh Journal of Animal Science, 2013)
Calcium salt of fatty acid was prepared by adding 3 different levels of saturated solution of calcium chloride (CaCl2) to soybean oil. It was found that fat content was not significantly affected by calcium chloride. However, calcium chloride had significant effect on other parameters like dry matter, fat, ash and sodium. The highest calcium and fat was obtained when 3.5 parts CaCl2 were added (p<0.01). It was also observed that sun drying and drying at room temperature had no significant effect on any parameter except dry matter content. Calcium salt of fatty acid had significant anti-protozoal effect (p<0.01) in sheep. Treated group showed reduced protozoal number without affecting the rumen pH and rumen ammonia nitrogen. It was also found that the number of rumen protozoa in rumen liquor was less at 12:00 p.m. than that at 3:30 p.m. when sheep were fed 3% calcium salt. DOI: http://dx.doi.org/10.3329/bjas.v42i2.18489 Bang. J. Anim. Sci. 2013. 42 (2): 109-113